2013
DOI: 10.1089/dna.2013.2138
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Profiles of PPP2R5C-siRNA-Treated Malignant T Cells

Abstract: Recently, alterations in the expression pattern of PPP2R5C associated with malignant transformation have been characterized, and PPP2R5C overexpression was demonstrated in leukemias. To confirm the role of PPP2R5C in proliferation and its molecular mechanism, three PPP2R5C-siRNAs and a scrambled nonsilencing siRNA control were used to treat Molt-4 and Jurkat T cells. After nucleofection, PPP2R5C expression and biological consequences based on a highly efficient and specific PPP2R5C-siRNA were demonstrated by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…PCR was performed in a 20 mL volume with *1 mL of cDNA, 0.5 mM of each primer pair, 9 mL of 2.5 · Real Master Mix (Tiangen Biotech, Beijing, China), and 9 mL of dH 2 O. The primer details are listed in Table 3 and the sequences and PCR conditions have been previously described (Huang et al, 2012;Li et al, 2012b;Chen et al, 2013). The relative amount of the genes of interest and the b2M reference gene was measured in two independent assays.…”
Section: Patient Selectionmentioning
confidence: 99%
“…PCR was performed in a 20 mL volume with *1 mL of cDNA, 0.5 mM of each primer pair, 9 mL of 2.5 · Real Master Mix (Tiangen Biotech, Beijing, China), and 9 mL of dH 2 O. The primer details are listed in Table 3 and the sequences and PCR conditions have been previously described (Huang et al, 2012;Li et al, 2012b;Chen et al, 2013). The relative amount of the genes of interest and the b2M reference gene was measured in two independent assays.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Furthermore, RNA sequencing analysis suggests a significant attenuation of CCND1 expression in PPARγ-silenced PMVECs (Table S1B). CCND2 is commonly upregulated upon Wnt activation associated with proliferation, (Yasui et al, 2006), whereas downregulation of PPP2R5C inhibits cell proliferation (Chen et al, 2013). Moreover, Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Two different mutations in lung cancer and intestinal cancer can disrupt B56γ -P53 interaction (12,20). It has been showed that PPP2R5C suppression by RNAi can inhibit the proliferation of the Molt4 and Jourkat T cells (21). It also has been showed that the proliferation of the PPP2R5C-siRNAtreated CML cell line was decreased in K562 Cell line (22).…”
Section: Discussionmentioning
confidence: 99%